THE EFFECT OF STORYTELLING MEDIA USE ON THE SUCCESS OF CLASS IV & V PRIVATE ELEMENTARY SCHOOL CHRISTIAN EDUCATION LEARNING FROM THE ELIDA MEDAN - Dedi Syahputra Waruwu; Regina BM Nainggolan; Elfrida Siringo-ringo (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2020)
This study aims to reveal the influence of the use of storytelling media in the teaching of Christian Religious Education (PAK) for grades IV and V in the private elementary school of the Elida Christian College Foundation in Medan. This research uses experimental quantitative research. The sample of this research was 30 people. The instrument used was a questionnaire and the scale used was a Likert scale. The research data were analyzed using statistical techniques. The results of this study indicate that Christian Religious Education teachers at the Elida Christian Education Foundation Private Elementary School using storytelling media are categorized as "Good". This means that Christian Religious Education teachers at the Elida Christian Education Foundation's Private Elementary School in Medan have used storytelling media in Christian Religious Education lessonsKeyword : Storytelling media.Educational learning of christianity.